2020
DOI: 10.1002/ehf2.12877
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose cotransporter‐2 inhibitor was associated with an improvement in left ventricular systolic function in patients with type 2 diabetes mellitus with impaired left ventricular systolic function

Abstract: Aims Recent studies indicated that sodium glucose cotransporter-2 inhibitors (SGLT2i) reduced heart failure hospitalization in patients with type 2 diabetes mellitus (T2DM). However, whether SGTL2i can improve left ventricular (LV) systolic and diastolic function remained unclear. This study aimed to compare the change in echocardiographic parameters in T2DM patients receiving SGLT2i with a different baseline LV ejection fraction (LVEF). The change in echocardiographic parameters was also compared between T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…To the best of our knowledge, this is one of the first studies showing an improved biventricular function in chronic HF after therapy with SGLT2i in a real‐world registry. After 3 months of therapy with SGLT2i an improvement of LV function, in terms of LVEF and GLS, and an improvement of LV dimensions (LVEDD and ESV) were found; these results are in line with Chan et al (2020), who demonstrated that SGLT2i therapy was associated with an improvement in LV systolic function in patients with T2DM with reduced and moderately reduced LVEF. More recently results from a meta‐analysis by Yu et al showed that LVEF improved only in T2DM patients with HFrEF (Yu et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To the best of our knowledge, this is one of the first studies showing an improved biventricular function in chronic HF after therapy with SGLT2i in a real‐world registry. After 3 months of therapy with SGLT2i an improvement of LV function, in terms of LVEF and GLS, and an improvement of LV dimensions (LVEDD and ESV) were found; these results are in line with Chan et al (2020), who demonstrated that SGLT2i therapy was associated with an improvement in LV systolic function in patients with T2DM with reduced and moderately reduced LVEF. More recently results from a meta‐analysis by Yu et al showed that LVEF improved only in T2DM patients with HFrEF (Yu et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…SGLT2i an improvement of LV function, in terms of LVEF and GLS, and an improvement of LV dimensions (LVEDD and ESV) were found; these results are in line withChan et al (2020), who demonstrated that SGLT2i therapy was associated with an improvement in LV systolic function in patients with T2DM with reduced and moderately reduced LVEF. More recently results from a meta-analysis byYu et al showed that LVEF improved only in T2DM patients with HFrEF(Yu et al, 2021).Tanaka et al (2020), in accordance with our results, showed a significant improvement of GLS 6 months after administration of dapagliflozin in CHF patients with T2DM.…”
supporting
confidence: 87%
“…Additionally, SGLT2i inhibit the sodium/hydrogen exchanger 1 and 3, lowering the levels of sodium and calcium in the heart and kidney, respectively. Those exchangers are associated with fibrosis, hypertrophy and sodium retention in the heart [44] , [38] , [39] , [40] , [41] . Other cardiorenal benefit pathways are reduction in systemic blood pressure and plasma uric acid, and increase in natriuresis and hematocrit [41] .…”
Section: Discussionmentioning
confidence: 99%
“… Lin et al 2021 [ 50 ] Rats with mitral regurgitation induced left heart dilatation and functional decline Dapagliflozin partially restored LVEF and significantly diminished cardiac fibrosis and apoptosis Shi et al 2019 [ 51 ] Transverse aortic constriction induced cardiac remodeling in mice then treated with dapagliflozin Dapagliflozin improved cardiac systolic function, and inhibited myocardial fibrosis and cardiomyocyte apoptosis Yerra et al 2022 [ 52 ] Transverse aortic constriction induced cardiac remodeling in mice then treated with empagliflozin Empagliflozin attenuated LV enlargement in mice Chen et al [ 53 ] Model of diabetes using male BTBR ob/ob mice; dapagliflozin, ticagrelor, or both administered for 12 weeks Both agents improved left ventricular end-systolic and end-diastolic volumes as well as LVEF Byrne et al 2020 [ 54 ] Rodent model of HF administered empagliflozin Empagliflozin associated with reduced cardiac inflammation via blunting activation of the NLRP3 inflammasome in a Ca(2+)-dependent manner Santos-Gallego et al 2019 [ 55 ] Heart failure induced in nondiabetic pigs that were randomized to empagliflozin or placebo for 2 months Empagliflozin ameliorated adverse cardiac remodeling and HF and improved myocardial energetics Li et al, 2021 [ 56 ] Mice subjected to sham surgery or transverse aortic constriction and after 2 weeks given empagliflozin or vehicle was for 4 weeks. Empagliflozin increased glucose and fatty acid oxidation in failing hearts, while reducing glycolysis Human studies Thirunavukarasu et al [ 57 ] Patients with T2D underwent cardiac magnetic resonance and (31)P-MRS scans before and after 12 weeks of empagliflozin Improvements seen in LVEF, global longitudinal strain, and mean myocardial cell volume Chan et al [ 58 ] Compare changes in echocardiographic parameters ...…”
Section: Methodsmentioning
confidence: 99%
“…Chan et al published the results of a study in which they enrolled 665, 119, and 132 patients with T2D and preserved (≥ 50%), moderately reduced (40–50%), and reduced baseline LVEF (< 40%) who were receiving with SGLT-2i [ 58 ]. In addition, 212 patients receiving a DPP-4i were enrolled.…”
Section: Methodsmentioning
confidence: 99%